PERANCANGAN WIREFRAME WEBSITE PELACAKAN PERSURATAN DI YAYASAN TARAKANITA - Lina Lina (LPPM UPN Veteran Jakarta, 2023)
Tarakanita Foundation is a Catholic Education Foundation which is engaged in educational services. Tarakanita Foundation oversees several schools operating in various regions in Indonesia. Along with the pandemic due to the Covid-19 virus, the Tarakanita Foundation has also complied with the Indonesian government's regulations regarding the enactment of restrictions on community activities. For this reason, Tarakanita Foundation also limits the number of personnel (leaders and staff) who are tasked with carrying out daily operational activities at the office location. As a result, the administrative activities of correspondence at Tarakanita Foundation which had been carried out in the form of manual recording by staff by being physically present at the office became somewhat hampered. Another way that has been taken by the Tarakanita Foundation is to use social media such as the Whatsapp application, using e-mail, and other applications to coordinate related to mail administration. However, all existing applications are only able to send or receive letters from one party to another without being able to search or record mail history. In fact, it is not uncommon for a letter to go through many stages of a process that involves more than two parties. Realizing the limitations it faces, the Tarakanita Foundation needs a new website-based media that will be designed to allow unit leaders and related staff to do online mail processing that can be done anytime and anywhere. As a first step, the community service activity team (PKM) will design a wireframe website for tracking letters for the Tarakanita Foundation. The process of creating a website wireframe will allow all components on the website such as banners, headers, content, footers, links, forms, and others to be arranged according to the desired layout. This stage is very important to do before the website will be transformed into a neater visual design and the development of a complete website application in the end.